Collagen–chitosan–laminin hydrogels for the delivery of insulin‐producing tissue. (30th October 2013) - McEwan, Kimberly; Padavan, Donna T.; Ellis, Cara; McBane, Joanne E.; Vulesevic, Branka; Korbutt, Gregory S.; Suuronen, Erik J.
Abstract: Islet transplantation is an emerging strategy for treating patients with type 1 diabetes mellitus. Although the proof of concept for cellular replacement therapy in diabetes has been firmly established, vascularity of the transplant site and the long‐term survival and function of transplanted islets remains suboptimal. In the present study, human circulating angiogenic cells (CACs) and porcine islet cells embedded in collagen–chitosan hydrogels, with and without laminin, were investigated as potential engineered biomaterials for the treatment of type 1 diabetes. Hydrogels were evaluated in vitro for their physical properties (compression, degradation, porosity and wettability) and cell compatibility. Increasing the chitosan content in the collagen‐based hydrogel resulted in increased stiffness ( p ≤ 0.04) and time to gelation ( p < 0.001), but reduced porosity (from 22–28% to 16–19%). The material design formulations (10:1 vs 20:1 collagen:chitosan ratio) directly affected the cell properties. The viability of both human CACs and porcine islets embedded in the 20:1 collagen–chitosan matrix was higher at 24 h compared to the 10:1 formulation. For islet function, glucose stimulation indices for the 20:1 formulation at 24 h compared favourably with values reported in the literature, more so than the 10:1 formulations. While laminin improved the short‐term viability of CACs, its presence did not confer any benefit to islet viability or function. Overall, the design features outlined in this study provided the degree of control required to establish viable tissue with potential for islet transplantation and neovascularization. Copyright © 2013 John Wiley & Sons, Ltd.